(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article deals with the ontology of the ethical teachings of Yusuf Khass Hajib, the great poet and thinker of the medieval East in the context of the philosophical reconstruction of his socio-ethical heritage from the point of view of modern discourse. The problem of ethical ontology is, first of all, the question of the essence of man, his place and purpose in society. The value paradigms of ideal social life were found by Yusuf Khass Hacib in the life of a community of people that exists as a harmonious whole based on justice and knowledge.